(untitled) - Gray, William S. (New Jersey, 2003)
This book provides information on every facet and department of the hotel. Operation of a property management system is discussed with sample reports for readers are provided. The operation of restaurant point of sale systems is also discussed, with related sample reports included. This comprehensive, easy-to-follow guidebook covers all aspects of hotel and motel development, hotel management, hotel operation, hotel accounting and controls, and the future of the industry. For hotel management and training professionals.
Keywords: Hotel management,Motel management,Health resorts,Casinos; Management,Management